Pigmentiphaga humi sp. nov., isolated from soil amended with humic acid. Issue 6 (8th April 2019) - Kämpfer, Peter; Busse, Hans-Jürgen; Criscuolo, Alexis; Bizet, Chantal; Clermont, Dominique; McInroy, John A.; Glaeser, Stefanie P.
Abstract : A slightly beige-pigmented, Gram-stain-negative, rod-shaped bacterium, strain IMT-318 T, was isolated from soil in a field located in Malvern, Alabama, USA. Phylogenetic analysis based on the 16S rRNA gene placed the strain within the genus Pigmentiphaga with highest 16S rRNA gene sequence similarity of 98.74 % and 98.67 % to the type strains of Pigmentiphaga kullae and Pigmentiphaga daeguensis, respectively. Sequence similarities to all other species of the genus were below 98.0 %. Results of the chemotaxonomic analysis, however, showed clear similarities to the genus Pigmentiphaga . The main cellular fatty acids of the strain were C16 : 0, C18 : 1  ω7 c, C17 : 0 cyclo and C19 : 0 cyclo ω8 c . The major quinone was ubiquinone Q-8. The polar lipid profile was composed of phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified aminophospholipid. In the polyamine pattern, putrescine and 2-hydroxyputrescine were predominant. The diamino acid of the peptidoglycan was meso- diaminopimelic acid. Based on phylogenetic, chemotaxonomic and phenotypic analyses, we propose a new species of the genus Pigmentiphaga, with the name Pigmentiphaga humi sp. nov. and strain IMT-318 T (=LMG 30658 T =CIP 111626 T =CCM 8859 T ) as the type strain.